Phytochemical properties and antimicrobial and antioxidant activities of Uvaria micrantha (A.DC.) Hook. f. & Thomson - Yong, Kok Kian (2018)
Uvaria micrantha (A.DC.) Hook. f. &Thomson is a medicinal plant species used by local people in Malaysia. However there are limited scientific evidence to validate the medicinal properties of U. micrantha. In this study, phytochemical screening of the leaf extracts of U. micrantha using methanol, hexane and ethyl acetate was conducted. The antimicrobial and antioxidant activities of extracts were determined using agar disk-diffusion and 2, 2-diphenyl-1-picryl-hydrazyl (DPPH) tests. The methanol extract was rich in phytochemicals such as alkaloids, phenols and terpenoids, while the hexane and ethyl acetate extracts had only terpenoids. Antimicrobial activity against the bacteria species Staphylococcus aureus was only detected in the methanol extract. Comparing to the ascorbic acid as positive control, methanol extract showed higher antioxidant activities than the hexane and ethyl acetate extracts. The presence of phytochemicals and antimicrobial and antioxidant activity in the leaf part of U. micrantha provides support to its uses as medicinal plant by the locals.